ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI PADA MATERI LARUTAN PENYANGGA DENGAN MODEL PEMBELAJARAN PREDICT OBSERVE EXPLAIN - Fernanda, Adisti; Haryani, Sri; Prasetya, Agung Tri; Hilmi, Mahmud (Universitas Negeri Semarang, 2019)
Critical thinking skill is considered as important skill to be trained and developed in chemistry learning. Predict, Observe and Explain (POE) is one of many learning models that expected to be able to develop students' critical thinking skills. This study aims to determine the achievement of students in seven indicators of critical thinking after getting learning with the POE model in the buffer solution material. The instruments used for data collection are critical thinking skill tests, questionnaires about students’ respond, and interviews. The research method that used is mix methods which use combination of quantitative and qualitative data. The results of data analysis showed that high group students still had difficulty in making induction. Students in the moderate group are still having difficulties in considering observation reports, making induction, making decision, and identifying assumptions. Low group students still find it difficult to consider the credibility of a source, observing, making induction, making decision, and identifying assumptions. While the most successful indicator is the indicator of asking and answering question, meanwhile the least successful indicator is indicator of making induction.